The antimicrobial peptides secreted by the chromaffin cells of the adrenal medulla link the neuroendocrine and immune systems: From basic to clinical studies - Scavello, Francesco; Kharouf, Naji; Lavalle, Philippe; Haikel, Youssef; Schneider, Francis; Metz-Boutigue, Marie-Hélène (Frontiers in Immunology, 2022)
The increasing resistance to antibiotic treatments highlights the need for the development of new antimicrobial agents. Antimicrobial peptides (AMPs) have been studied to be used in clinical settings for the treatment of infections. Endogenous AMPs represent the first line defense of the innate immune system against pathogens; they also positively interfere with infection-associated inflammation. Interestingly, AMPs influence numerous biological processes, such as the regulation of the microbiota, wound healing, the induction of adaptive immunity, the regulation of inflammation, and finally express anti-cancer and cytotoxic properties. Numerous peptides identified in chromaffin secretory granules from the adrenal medulla possess antimicrobial activity: they are released by chromaffin cells during stress situations by exocytosis via the activation of the hypothalamo-pituitary axis. The objective of the present review is to develop complete informations including (i) the biological characteristics of the AMPs produced after the natural processing of chromogranins A and B, proenkephalin-A and free ubiquitin, (ii) the design of innovative materials and (iii) the involvement of these AMPs in human diseases. Some peptides are elective biomarkers for critical care medicine, may play an important role in the protection of infections (alone, or in combination with others or antibiotics), in the prevention of nosocomial infections, in the regulation of intestinal mucosal dynamics and of inflammation. They could play an important role for medical implant functionalization, such as catheters, tracheal tubes or oral surgical devices, in order to prevent infections after implantation and to promote the healing of tissues.